1999
DOI: 10.1017/s0033291799008594
|View full text |Cite
|
Sign up to set email alerts
|

Criminality and antisocial behaviour in unselected men with sex chromosome abnormalities

Abstract: The findings of this study carry the advantage of not being affected by ascertainment bias and the disadvantage of having low power. It provides evidence for a slightly increased liability to antisocial behaviour in XYY men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 19 publications
0
35
1
1
Order By: Relevance
“…7 Unfortunately, these findings were often followed by replication failures. 8 Scientists have developed a more intricate understanding of the nature of the relationship between genotypes and phenotypes, whereas lay people have not, reflecting their largely inaccurate mental representations of genetics. 9,10 The perception of genetic etiology engenders cognitive fallacies, termed genetic essentialist biases.…”
Section: Introductionmentioning
confidence: 99%
“…7 Unfortunately, these findings were often followed by replication failures. 8 Scientists have developed a more intricate understanding of the nature of the relationship between genotypes and phenotypes, whereas lay people have not, reflecting their largely inaccurate mental representations of genetics. 9,10 The perception of genetic etiology engenders cognitive fallacies, termed genetic essentialist biases.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have emphasize that people with KS are friendly and open to interactions, do not usually have major problems with social interaction and adaptation, although they may be shy, sensitive and unassertive (6.44). KS subjects have difficulties in the construction of satisfying social relationships, with antisocial behavior in adolescence and a more unstable occupational history, but a minority of them meets criteria for antisocial behavior disorder in adulthood [8]. Although children with KS are reported by clinicians to be hyperactive and to show difficulties in concentration, some studies have showed that children with KS have a docile temperament and lower activity levels compared with unaffected peers [10].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have emphasize that people with KS are friendly and open to interactions, do not usually have major problems with social interaction and adaptation, although they may be shy, sensitive and unassertive [6,7]. Other studies have showed that males with KS have difficulties in the construction of satisfying social relationships, with antisocial behavior in adolescence and a more unstable occupational history, but a minority of them meets criteria for antisocial behavior disorder in adult hood [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some research observed a great number of violent conduct and crimes in subjects suffering from Jacobs' Syndrome [51][52][53], while others denied a relationship between an extra Y and deviance [24,[54][55][56][57]. According to other studies, the connection between this chromosome abnormality and dysfunctional behavior was rather considered possibly due to associated intellectual deficits or to underlying aggressiveness [18,53,58].…”
Section: Xyy Syndromementioning
confidence: 99%
“…Therefore, some research observed a great number of violent conduct and crimes in subjects suffering from Jacobs' Syndrome [51][52][53], while others denied a relationship between an extra Y and deviance [24,[54][55][56][57]. According to other studies, the connection between this chromosome abnormality and dysfunctional behavior was rather considered possibly due to associated intellectual deficits or to underlying aggressiveness [18,53,58]. Contrariwise, other authors hypothesized that these men are more easily recognized as offenders because of their high stature and stocky build, which would make them more identifiable [59][60][61][62][63][64][65][66][67][68][69].…”
Section: Xyy Syndromementioning
confidence: 99%